Ovarian morphology and plasma hormonal concentration during different phases of reproductive cycle in buffaloes (Bubalus bubalis) - Bansal, Neelam; Jindal, Rajesh; Nayyar, Shashi; Malik, V S (The Indian Journal of Animal Sciences, 2011)
Gross morphological and hormonal studies were made on 30 apparently healthy adult Murra buffaloes. On the basis , of colour, consistency and diameter of the follicles and coropa lutea observed on the surface of ovaries, animals were grouped into follicular, early-luteal or late-luteal phases of reporductive cycle along with various ranges of corpus luteum. This categorization, was confirmed with circulating levels of gonadal hormones plasma estradiol- 17-Beta and progesterone which were maximum (25.73 +- 9.75 pg/ml and 2.32 +-0.62 ng/ml) during presumed follicular and luteal phases, respectively.